Scaling women smallholder farmer’s access to mechanization: Analysis of farmer groups’ services in Bangladesh - Jones, Maria; Lindgren, Samantha; Mozumdar, Lavlu; Alrawashdeh, Ghaida (United Nations Economic and Social Commission for Asia and the Pacific, 2023)
Sustainable mechanization can help reduce women smallholder farmers’ time and labor burden while increasing farm productivity and building resilience. However, the reality is that most agricultural innovations and technologies do not cater to women’s needs or preferences and are primarily designed for middle-income male farmers. While the adoption of mechanization in Bangladesh is rapidly increasing, women smallholder farmers face sociocultural constraints that can make operating machines difficult. Service providers have made agricultural mechanization more accessible to smallholder farmers; however, machinery service providers are predominantly men, which makes it difficult for women to learn about and access service providers. The objective of this study was to determine how to best scale agricultural mechanization in conservative sociocultural settings in a gender-responsive manner. A needs assessment (n = 41) conducted in the Mymensingh and Barisal districts of Bangladesh through semi-structured interviews and focus groups revealed three key lessons for the scaling of mechanization to benefit women: a pivot in how we think about adoption is required, male mechanization service providers must be equipped to reach women farmers, and sustainable business models for group ownership of mechanization must be developed.